1997
DOI: 10.1021/la960053n
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and XPS Characterization of Glassy Carbon Electrode Surface Effects on the Preparation of a Monomeric Molybdate(VI)-Modified Electrode

Abstract: Evaluation of electrochemical surface pretreatment methods on the preparation of monomeric molybdate(VI)-modified glassy carbon electrode (GCE) in H2SO4 is studied. The results show that the cathodically treated GCE is unusually highly activated toward Mo(VI) adsorption, but the anodized electrode does not respond, unlike the previous reports for the other adsorbed systems. The analyses of the voltammograms of Mo(VI) on a cathodized electrode show three pairs of reversible peaks with a surface excess on the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 66 publications
7
65
1
Order By: Relevance
“…The situation is further clarified in the XPS spectrum of the same sample shown in Fig.2c. The C1s core level spectrum, fitted in a similar fashion as before, reveals a substantial signal of sp 3 hybridization [47][48][49] along with other carbon functionalities, such as C-N [50,51], C-OH [52,53], C=O [47,52,53], COOH/R [47,52,53], CF-C/C-CF n [54][55][56] as previously reported in the literature. The asymmetry factor on the graphitic peak is increased to 0.1, considerably higher than the as grown sample.…”
Section: Transferred Graphenementioning
confidence: 61%
“…The situation is further clarified in the XPS spectrum of the same sample shown in Fig.2c. The C1s core level spectrum, fitted in a similar fashion as before, reveals a substantial signal of sp 3 hybridization [47][48][49] along with other carbon functionalities, such as C-N [50,51], C-OH [52,53], C=O [47,52,53], COOH/R [47,52,53], CF-C/C-CF n [54][55][56] as previously reported in the literature. The asymmetry factor on the graphitic peak is increased to 0.1, considerably higher than the as grown sample.…”
Section: Transferred Graphenementioning
confidence: 61%
“…60,[69][70][71][72] For most couples, anodic treatment of a carbon electrode inhibits the redox reaction while cathodic treatment enhances it. Thus, the effects of electrode treatment on V IV -V V are consistent with results for other systems but the contrasting effects on V II -V III are remarkable.…”
Section: Comparison Of Vmentioning
confidence: 99%
“…McCreery et al reported that the N O1s / N C1s ratio can vary in the window of 0.04 to 0.15 under various GCE polishing treatments [25]. Ilangovan and Pillai reported that surface carbon density is an important factor to increase the N O1s /N C1s ratio and it can be improved to 0.51 upon anodization of the GCE surface [26]. The SPE* seems to have a smaller amount surface carbon density over that of GCE, however, the additional chloride peak on the surface can assist for the stabilization of Pd nanoparticles on the SPE*.…”
Section: X-ray Photoelectron Spectroscopy Characterizationmentioning
confidence: 99%